Efikasi Diri Dan Dukungan Sosial Pasien Hemodialisa Dalam Meningkatkan Kepatuhan Pembatasan Cairan - Ela Susilawati; Kamaluddin Latief; K Khomarudin (Universitas Faletehan, 2018)
The increasing of intradialitic weight due to non-adherence to fluid intake of patients who undergoing hemodialysis is resulting in chronic buildup of fluid and risks for cardiovascular disorders and hypertension, as well as increased mortality and morbidity rate in patients with chronic renal failure. Social support is one of factors that support patient compliance in the therapy. This research design was mixed methods with sequential explanatory. Population in this study were all patients with chronic renal failure who underwent hemodialysis in Rumah Sakit Umum Tangerang. Quantitative sample were selected by using total sampling technique of 76 patients, and the number of qualitative samples taken by using purposive sampling technique of 6 patients. Data were collected with Chronic Kidney Disease Self-Efficacy Instrument and Multidimentional Scale Perceived Social Support, as well as interviews. Quantitative data analized with pearson correlation, but qualitative data analized by using Miles and Huberman model analysis techniques. Pearson correlation showed that there was a relationship between efficacy and social support with fluid restriction compliance (r = 0.476 p = 0.001) and (r = 0.308 p = 0.007). Based on the results of in-depth interviews found that the suffer from thirst cause patients to be non-compliance of fluid intake program restriction. It is expected that the hospital provides a special room to the patient's family, and the nurse gives high motivation to the patient while undergoing the therapy regimen.